THE PURPOSES OF DENIAL IN DELIBERATIVE FUNCTIONS /SURAT AL-BAQARAH AS A MODEL - Asawer Hatem Khalil (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2021)
From the foregoing, it became clear to us that the pragmatic theory is concerned with the role played by the interlocutors in the social world, as they do not interact with each other through language only, but they accept that interaction and cooperate on it. Also, it removes the ambiguity of the elements of linguistic communication and explains the methods of inference and the processing of utterances1 And we learned that the deliberative functions are mostly divided into 1- verbal verbs 2- indices 3- presupposition 4- dialogical imperative In this research, we will deal with the intention of denial in Surat Al-Baqarah through the function of speech verbs, indices, and presupposition.